2017
DOI: 10.1016/j.ijid.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Health systems in the Republic of Congo: challenges and opportunities for implementing tuberculosis and HIV collaborative service, research, and training activities

Abstract: The Republic of Congo is on the World Health Organization (WHO) list of 'high burden' countries for tuberculosis (TB) and HIV. TB is the leading cause of death among HIV-infected patients in the Republic of Congo. In this viewpoint, the available data on TB and HIV in the Republic of Congo are reviewed, and the gaps and bottlenecks that the National TB Control Program (NTCP) faces are discussed. Furthermore, priority requirements for developing and implementing TB and HIV collaborative service activities are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
(60 reference statements)
1
10
0
2
Order By: Relevance
“…Our data also reveal the need to strengthen capacity and skills of CHWs, who rarely conducted home visits on nutrition and/or child illness, with the exception of vaccinations. Although some facility‐ and community‐level health providers were reported to have been trained in IYCF, gaps in services remain due to lack of resources, SBCC materials, and a solid understanding of key nutrition counselling messages to provide families in the DRC (Linguissi et al, ; Maketa et al, ). At the community level, nutrition counselling on IYCF, as part of the iCCM, is critical to improving nutrition outcomes, according to recent evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also reveal the need to strengthen capacity and skills of CHWs, who rarely conducted home visits on nutrition and/or child illness, with the exception of vaccinations. Although some facility‐ and community‐level health providers were reported to have been trained in IYCF, gaps in services remain due to lack of resources, SBCC materials, and a solid understanding of key nutrition counselling messages to provide families in the DRC (Linguissi et al, ; Maketa et al, ). At the community level, nutrition counselling on IYCF, as part of the iCCM, is critical to improving nutrition outcomes, according to recent evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence to GeneXpert algorithm, interrupted supply of cartridges, lack of replacement of damaged modules, poor maintenance, and poor recording and reporting limit usefulness of GeneXpert in TB diagnosis [14,26,27]. Poor adherence to national guidelines [11,22,23]; dilapidated infrastructure [5,12,23] weak TB/HIV integration [10,12,14,24,28]; lack of public-private mix [10,12,23] and poor integration into general health services hinder effective TB service delivery [5,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] These studies are important to TB and HIV programs because they contribute to improving these actions and help identify the operational challenges to be overcome to control both diseases. [16][17][18][19][20][21] A bibliographic search carried out in the Latin America and Caribbean Center on Health Science Information (LILACS) and PubMed (MEDLINE) databases aiming at finding operational studies related to care to TB/HIV coinfection published between 2012 and 2017 identified 13 articles pertinent to the examined subject, which were classified into five main axes according to their results: Active search for TB/HIV; [22][23][24] TB/HIV diagnosis and treatment; [25][26] Educational activities to control TB/HIV; 27 Interaction between TB/HIV-related services; [28][29] and Evaluation of operational indicators of the TB/HIV program. [16][17][18][19][20] The last one is the focus of the present study, in addition to contributing to the production of knowledge about care to TB/HIV coinfection in the Brazilian context.…”
Section: Introductionmentioning
confidence: 99%